Leaf morphology displays no detectable spatial organisation in the relict Quercus afares Pomel compared to the co-occurring parental species Q. canariensis Willd. and Q. suber L - Mhamdi, Samah; Brendel, Oliver; Montpied, Pierre; Ghouil-Amimi, Hanah; Hasnaoui, Ibrahim; Dreyer, Erwin (Annals of Forest Science, 2013)
•Context Oak species display a large within-species diversity combined with significant gene flow between species. Quercus afares Pomel is an endemic species that grows as a small relict population in Northern Tunisia, together with Quercus suber L. and Quercus canariensis Willd. It is considered to be a fixed hybrid between the two latter. •Aims We tested (1) whether this population of Q. afares is declining with respect to the neighbouring populations of the two other species and (2) whether the spatial distribution of leaf morphology is random among individuals within this small population of Q. afares or influenced by the neighbouring species. •Methods Spatial distribution and diameter at breast height were recorded in the population of Q. afares. We identified two perpendicular transects across the population reaching from areas dominated by Q. canariensis to areas dominated by Q. suber and defined 20 plots along each. Eleven traits were assessed on 10 leaves collected from the upper crown of trees from the three species. A multiple correspondence analysis and an ANOVA were used to test for within and between-species diversity in leaf morphology. •Results Q. afares individuals occurred at a low frequency among the two other species. Nevertheless, Q. afares showed no particular evidence of decline with respect to the two other species. Leaf traits displayed a large inter-specific variability with very little overlap between Q. afares and Q. suber and some between Q. afares and Q. canariensis. A high level of diversity was detected for these traits within Q. afares, but we were unable to unravel any spatial organisation of this diversity; in Q. afares, leaf traits varied independently of the presence of neighbouring Q. suber or Q. canariensis. •Conclusion Q. afares seems to be a fixed species with specific leaf traits that are independent of that of the species of the neighbouring trees. This population is not suffering a detectable trend towards decline except for the lack of any visible regeneration below any of the three species.
Keywords: Endemic oak species; Hybridization; leaf morphology; Mixed oak stands

Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L.; Cotti, C.; Cristofolini, G. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract Random Amplified Polymorphic DNA (RAPD) and Inter-Simple Sequence Repeats (ISSR) markers were employed to examine samples from Quercus cerris, Q. suber and Q. crenata in order to test the hypothesis of the hybrid origin of Q. crenata from Q. cerris and Q. suber in a part of its distribution area where the two putative parents do not overlap at present. Leaves from 21 Q. crenata and 37 Q. cerris individual trees were collected at natural sites in northern Italy, where Q. suber is currently lacking; 21 Q. suber and six Q. crenata plants from central Italy were also analysed. Results from Unweighted Pair Group Method with Arithmetic mean (UPGMA) analysis and principal component analysis (PCA) implied that exchange of neutral markers has been considerable between the three species, while differences in morphological characters have remained comparatively stable. The Mantel test indicated low correlation between RAPD- and ISSR-based similarity matrices, showing that the two screening techniques reveal unrelated estimates of genetic relationships. Hybrid indices computed for both markers displayed an intermediate position of Q. crenata individuals between the two putative parents shifted toward Q. cerris. Results from the present study corroborate the hypothesis of a hybrid origin for Q. crenata occurring in northern Italy, and suggest asymmetrical backcrossing with Q. cerris acting as the recurrent parent.
From Duplicate 2 (Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L; Cotti, C; Cristofolini, G)
Keywords: DNA markers; Hybridization; introgression; ISSR; RAPD

Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L.; Cotti, C.; Cristofolini, G. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract Random Amplified Polymorphic DNA (RAPD) and Inter-Simple Sequence Repeats (ISSR) markers were employed to examine samples from Quercus cerris, Q. suber and Q. crenata in order to test the hypothesis of the hybrid origin of Q. crenata from Q. cerris and Q. suber in a part of its distribution area where the two putative parents do not overlap at present. Leaves from 21 Q. crenata and 37 Q. cerris individual trees were collected at natural sites in northern Italy, where Q. suber is currently lacking; 21 Q. suber and six Q. crenata plants from central Italy were also analysed. Results from Unweighted Pair Group Method with Arithmetic mean (UPGMA) analysis and principal component analysis (PCA) implied that exchange of neutral markers has been considerable between the three species, while differences in morphological characters have remained comparatively stable. The Mantel test indicated low correlation between RAPD- and ISSR-based similarity matrices, showing that the two screening techniques reveal unrelated estimates of genetic relationships. Hybrid indices computed for both markers displayed an intermediate position of Q. crenata individuals between the two putative parents shifted toward Q. cerris. Results from the present study corroborate the hypothesis of a hybrid origin for Q. crenata occurring in northern Italy, and suggest asymmetrical backcrossing with Q. cerris acting as the recurrent parent.
From Duplicate 2 (Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L; Cotti, C; Cristofolini, G)From Duplicate 2 (Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L; Cotti, C; Cristofolini, G)The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: DNA markers; Hybridization; introgression; ISSR; RAPD

Frequent cytoplasmic exchanges between oak species that are not closely related: Quercus suber and Q. ilex in Morocco - Belahbib, N.; Pemonge, M.-H. H.; Ouassou, A.; Sbay, H.; Kremer, A.; Petit, R. J. (Molecular Ecology, 2001)
Chloroplast (cp) and mitochondrial (mt) DNA variation were studied in 97 populations of cork oak (Quercus suber) in Morocco; in 31 of these populations, holm oak (Quercus ilex), a clearly distinct species, also occurred and was compared with Q. suber. Three cpDNA and one mtDNA primer pairs were used in the survey, each in combination with one restriction enzyme. Six haplotypes belonging to two very divergent lineages were detected; one lineage predominates in each species, and is probably ancestral, as inferred from comparisons with other oak species. In the mixed-species populations, cytoplasmic genomes were frequently shared across species, as indicated by an introgression ratio of 0.63. This index is a new measure of the propensity of species to share locally genetic markers, varying from zero (complete differentiation) to one (no differentiation). By contrast, more closely related deciduous oak species (Q. robur, Q. petraea and Q. pubescens) have introgression ratios varying from 0.82 to 0.97. The introgression events appear to have been more frequent in the direction Q. ilex (female) × Q. suber (male), a finding which seems attributable to the flowering phenology of these two species. This asymmetry may have favoured immigration of Q. suber beyond its main range, in regions already colonized by Q. ilex. There, rare hybridization and further introgression through long distance pollen flow have established populations that are morphologically indistinguishable from Q. suber but that have cytoplasmic genomes originating from the local Q. ilex populations.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd accession-num: 11555243
Keywords: Chloroplast; Chloroplast: genetics; cpDNA; DNA; Evolution; Genetic; Genetic Markers; Genetic Variation; Genetic: genetics; geographical structure; Haplotypes; Hybridization; introgression; Mitochondrial; Mitochondrial: genetics; Models; Molecular; Morocco; mtDNA; PCR–RFLP; Quercus; Quercus: genetics; Trees; Trees: genetics

Frequent cytoplasmic exchanges between oak species that are not closely related: Quercus suber and Q. ilex in Morocco - Belahbib, N; Pemonge, M.-H. H; Ouassou, A; Sbay, H; Kremer, A; Petit, R J (Molecular Ecology, 2001)
Chloroplast (cp) and mitochondrial (mt) DNA variation were studied in 97 populations of cork oak (Quercus suber) in Morocco; in 31 of these populations, holm oak (Quercus ilex), a clearly distinct species, also occurred and was compared with Q. suber. Three cpDNA and one mtDNA primer pairs were used in the survey, each in combination with one restriction enzyme. Six haplotypes belonging to two very divergent lineages were detected; one lineage predominates in each species, and is probably ancestral, as inferred from comparisons with other oak species. In the mixed-species populations, cytoplasmic genomes were frequently shared across species, as indicated by an introgression ratio of 0.63. This index is a new measure of the propensity of species to share locally genetic markers, varying from zero (complete differentiation) to one (no differentiation). By contrast, more closely related deciduous oak species (Q. robur, Q. petraea and Q. pubescens) have introgression ratios varying from 0.82 to 0.97. The introgression events appear to have been more frequent in the direction Q. ilex (female) × Q. suber (male), a finding which seems attributable to the flowering phenology of these two species. This asymmetry may have favoured immigration of Q. suber beyond its main range, in regions already colonized by Q. ilex. There, rare hybridization and further introgression through long distance pollen flow have established populations that are morphologically indistinguishable from Q. suber but that have cytoplasmic genomes originating from the local Q. ilex populations.
Keywords: Chloroplast; Chloroplast: genetics; cpDNA; DNA; Evolution; Genetic; Genetic Markers; Genetic Variation; Genetic: genetics; geographical structure; Haplotypes; Hybridization; introgression; Mitochondrial; Mitochondrial: genetics; Models; Molecular; Morocco; mtDNA; PCR–RFLP; Quercus; Quercus: genetics; Trees; Trees: genetics

Evidence for hybridization between sympatric holm-oak and cork-oak in Spain based on diagnostic enzyme markers - Elena-Rossello, J. A.; Lumaret, R.; Cabrera, E.; Michaud, H. (Plant Ecology, 1992)
Hybridization has been detected in mixed populations of juvenile cork-oak and holm-oak individuals using three diagnostic enzyme loci coding for esterases, leucine amino peptidases and acid phosphatases respectively. Among the 35 studied individuals, 29, 5 and 1 were identified as holm-oak, cork-oak and hybrid respectively. Such diagnostic markers are likely to be useful to detect and remove hybrids at the juvenile stage in areas where the holm-oak is grown for acorn production and the cork-oak is cultivated for cork. This is necessary since hybrid adults produce neither cork nor acorns of high quality.
Keywords: cork-oak; enzyme markers; holm-oak; Hybridization; Quercus

Forest-tree genetics research: Quercus L. - Irgens-Moller, H (Economic Botany, 1955)
Oaks are the sources, not only of the most valuable timber among broad-leaved trees of the northern hemisphere, but also of cork, tannin, a dye, and food for man and beast. Their prolonged pre- flowering periods and other factors have discouraged genetic in- vestigation of them, but what little is known in that direction is here summarized.
Keywords: Hybridization; oak products; oak trees (Quercus spp.); propagation